A Comparative Research of Two English Translations of the Chapter "Comprehensive Discourse on Phenomena Corresponding to Yin and Yang" in Huangdi's Internal Classic - Zhi-Wei Zhou; Yan-Qing Li; Hai-Ying Li; Er-Liang Wang (Wolters Kluwer Health/LWW, 2022)
Abstract. Culture-loaded words refer to words with specific cultural connotations that can express an abstract or a specific concept, which may be related to religious beliefs or social customs, but do not exist in other languages and cultures. Therefore, culture-loaded words bring some difficulties to translation work. Huang Di Nei Jing (《黄帝内经》 Huangdi's Internal Classic) is the foundation of traditional Chinese medicine (TCM) theory, and is listed as the first of the four classics of TCM. It contains a large number of culture-loaded words, which embody the ancient Chinese traditional culture. The translation of culture-loaded words is a difficult but crucial point in the translation of Huangdi's Internal Classic and directly relates to the quality of the translation of Huangdi's Internal Classic as a whole. Taking the two English versions of Maoshing Ni and Li Zhaoguo as examples, this work identifies the culture-loaded words appearing in the chapter "Yin Yang Ying Xiang Da Lun" (阴阳应象大论 Comprehensive Discourse on Phenomena Corresponding to the Yin and Yang). This work studies the strategies and translation process of culture-loaded words in Huangdi's Internal Classic, with a view to contribute to the English translation of TCM classics.